2022
DOI: 10.3390/jcm11092415
|View full text |Cite
|
Sign up to set email alerts
|

References Values of Soluble α-Klotho Serum Levels Using an Enzyme-Linked Immunosorbent Assay in Healthy Adults Aged 18–85 Years

Abstract: α-Klotho protein is a powerful predictor of the aging process and lifespan. Although lowered circulating soluble α-Klotho levels have been observed in aged non-healthy individuals, no specific reference values across a wide range of ages and sex using an enzyme-linked immunosorbent assay (ELISA) are available for larger cohorts of healthy individuals. The present analytical cross-sectional study was aimed to establish the reference values of soluble α-Klotho serum levels in healthy adults by age and sex groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…Several available sKlotho assays failed to precisely determine the actual sKlotho level or the range of the sKlotho reference value ( Heijboer et al, 2013 ; Neyra et al, 2020b ). Interestingly, a recent study by Espuch-Oliver et al (2022) investigated the reference values of serum sKlotho in a larger sample with 346 healthy adults by ELISA. They observed that sKlotho levels differed significantly across ages, and sKlotho was inversely correlated with age in healthy subjects.…”
Section: How To Resolve the Controversymentioning
confidence: 99%
“…Several available sKlotho assays failed to precisely determine the actual sKlotho level or the range of the sKlotho reference value ( Heijboer et al, 2013 ; Neyra et al, 2020b ). Interestingly, a recent study by Espuch-Oliver et al (2022) investigated the reference values of serum sKlotho in a larger sample with 346 healthy adults by ELISA. They observed that sKlotho levels differed significantly across ages, and sKlotho was inversely correlated with age in healthy subjects.…”
Section: How To Resolve the Controversymentioning
confidence: 99%
“…In humans, serum levels of Klotho were also decreased with age [ 19 , 20 ]. Espuch-Oliver et al demonstrated that soluble levels of Klotho were decreased in healthy-aged individuals duo to aging-related physiological declines [ 21 ]. They proposed that the soluble Klotho (S-Klotho) level through ELISA measurement could be considered a simple and meaningful marker of aging that can improve quality of life for the elderly [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Espuch-Oliver et al demonstrated that soluble levels of Klotho were decreased in healthy-aged individuals duo to aging-related physiological declines [ 21 ]. They proposed that the soluble Klotho (S-Klotho) level through ELISA measurement could be considered a simple and meaningful marker of aging that can improve quality of life for the elderly [ 21 ]. Actually, the Klotho gene encoded several forms of Klotho protein, including membrane bound form and secreted form Klotho [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Klotho expression declines with age, renal failure, diabetes and neurodegenerative disease. The age-related decline in serum levels appears to be similar in men and women; and reference values have recently been reported (Espuch-Oliver et al, 2022). Notably, a recent study of American adults showed that low serum Klotho levels correlate with an increased all-cause death rate (Kresovich and Bulka, 2021).…”
Section: Introductionmentioning
confidence: 81%
“…Another relevant observation is the wide variability in Klotho levels between individuals. For instance, in a 18–35 age group approximately half of individuals had low levels, comparable to aged subjects, whereas the other half had high levels ( Espuch-Oliver et al, 2022 ). In the 55–85 age group, however, levels were more consistently low.…”
Section: Klotho and Neurodegenerative Diseasesmentioning
confidence: 99%